计算:(1+√5/2)^10+(1-√5/2)^10的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 23:56:56
计算:(1+√5/2)^10+(1-√5/2)^10的值计算:(1+√5/2)^10+(1-√5/2)^10的值计算:(1+√5/2)^10+(1-√5/2)^10的值因为奇次项为正负相抵,所以只算偶
计算:(1+√5/2)^10+(1-√5/2)^10的值
计算:(1+√5/2)^10+(1-√5/2)^10的值
计算:(1+√5/2)^10+(1-√5/2)^10的值
因为奇次项为正负相抵,所以只算偶次项:
C(10)2=45,C(10)4=210,C(10)6=C(10)4=210,C(10)8=C(10)2=45
(1+√5/2)^10+(1-√5/2)^10
=2[1+45(5/4)+210(25/16)+210(125/64)+45(625/256)+3125/1024]
=2[(1024+57600+336000+420000+112500+3125)/1024]
=930246/512
(1+√5/2)^10+(1-√5/2)^10
= 2( 1+ 10C2(√5/2)^2+10C4(√5/2)^4+10C6(√5/2)^6+10C6(√5/2)^8+10C10(√5/2)^10 )
1+2-3-4+5+6-7-8+.+2001+2002-2003-2004+2005+2006计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~计算~
计算2√27×1/3√5 计算2√27×1/3√5
根式计算:(2√5+1)[1/(1+√2)+.如下计算:
计算√32×1/2
计算2√27×1/3√5
计算 2X-2+X-1/5计算
二次根式计算:2√5(√5+1)(√5-1)+10√1/5
(5/2)^1/2*(2+√5)*(√10+2√2)的计算结果
计算:(1+√5/2)^10+(1-√5/2)^10的值
(-3√15+5√6)·(1/2)√10计算
计算3√5X2√10
-√3×√5 -√1/3×√27 计算
计算 -√19÷√95×√1/5
计算√(1/x^2+y^2)
-2√1-27分之19 计算
计算[(-√3)^4]^-1/2
计算(√3+i)^5/(-1+√3i)
3/10+1/5-1/3计算,